PENINGKATAN DAYA SAING KOPI RAKYAT DI KABUPATEN JEMBER - Henik Prayuginingsih; Teguh Hari Santosa; Muhammad Hazmi; Nanang Saiful Rizal (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2012)
Jember has 16.882 ha of coffee plantation, which  5.601,31 ha of them are smallholder coffee. Smallholder coffee is often identified has  low productivity and quality. This research wanted to know: (1)the advantage of smallholder coffee at District of Jember; (2) how to increase the advantage. Research was done on May – August 2012 (harvest periode) at Sub District of Silo, Sumberjambe, Ledokombo and Panti with 98 respondens which were choosen by  stratified random sampling methode.  The advantage was measured by  DRCR dan PCR, in order to increase the advantage using the result of Cobb-Douglas model of multiple regression analize on production function.  The  result show  that:  (1) there are two methode of post-harvest processing of coffee, they are wet process and dry process methode;(2) smallholder coffee at Jember has competitif and comparative advantage (PCR wet process methode is 0,3679 and dry process methode is 0,4261). (3) Balance fertilizing could increase  the advantage, but just comparative advantage (DRCR decrease to  0,4907 on wet process methode and 0,3566 on dry process methode), on the other side competitive advantage was a little decrease (PCR wet process methode is 0,5056  and  0,5089 on dry process methode).  Further more, balance fertilizing could increase the profit from IDR 17.804.906/ha/year to                IDR 21.103.109/ha/year on wet process methode and from IDR 8.965.371/ha/year to            IDR 17.112.813/ha/year on dry process methode. Key words: competitive advantage, comparative advantage, balance fertilizing